DETERMINING AND COMPARING THE PHYSICS ATTITUDE STATE AT A SOCIAL SCIENCE HIGH SCHOOL: AN EXAMPLE OF DENIZLI IBRAHIM CINKAYA SOCIAL SCIENCE HIGH SCHOOL - KAHRAMAN, Ozkan (The Eurasia Proceedings of Educational and Social Sciences, 2015)
The purpose of this study is to investigate and determine the Physics Attitude Level of Social Science Secondary High School students, to compare them based on gender and grade variables and to determine correlation between physics achievement and physics attitude. The sample of the study was selected as an accessible population by using sample of convenience way. It covers 409 students of preparatory, ninth, tenth and eleventh grade levels, 246 were female and 163 were male, attending at Social Science Secondary High School in Denizli. Survey method, the most common descriptive study methods of quantitative approach, was used. There was only one instrument to get data, Physics Attitude Questionnaire, consisting of thirty questions. It was applied to subjects and analyzed with SPSS 17.0. In the analysis of the data, independent sample t-test for comparisons based on gender and class variable, one way ANOVA test for comparisons based on class variable and Pearson correlation were used. As a result of the study, average level of physics attitude was found at all the grade levels. According to gender variable, significant difference was found in favor of boys in general and for ninth and tenth grade levels. According to class level variable, significant difference was found between both eleventh and ninth and eleven and preparatory grade levels in favor of preparatory and ninth grades. In addition to them, correlation between physics achievement and physics attitude was found significant in general and for ninth grade students.